2002
DOI: 10.1159/000046748
|View full text |Cite
|
Sign up to set email alerts
|

Effect of either Gamma-Tocotrienol or a Tocotrienol Mixture on the Plasma Lipid Profile in Hamsters

Abstract: Background/Aims: Tocotrienols has been shown to inhibit the 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase activity; however, the published animal and human studies yield conflicting results. We investigated the effects of a 4-week dietary supplement of either γ-tocotrienol (86% γ-T3) or a mixture of tocotrienols (29.5% α-T3, 3.3% β-T3, 41.4% γ-T3, 0.1% δ-T3: mix-T3) on the plasma lipid profile in hamsters receiving a high fat diet. Methods: The hamsters were randomized into 7 groups: no treatment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 22 publications
2
19
0
1
Order By: Relevance
“…The differences observed in the human studies were partly due to the use of various doses and sources of TRF and tocotrienols. In order to compare the results of animal and human studies, Raederstorff et al studied steady-state plasma γ-tocotrienol levels and plasma cholesterol levels in hamsters (50). They observed that the maximum effect of γ-tocotrienol was reached after 2 wk with the highest dose (263 mg/d/kg body weight); thereafter, the effect on cholesterol was plateaued.…”
Section: Discussionmentioning
confidence: 99%
“…The differences observed in the human studies were partly due to the use of various doses and sources of TRF and tocotrienols. In order to compare the results of animal and human studies, Raederstorff et al studied steady-state plasma γ-tocotrienol levels and plasma cholesterol levels in hamsters (50). They observed that the maximum effect of γ-tocotrienol was reached after 2 wk with the highest dose (263 mg/d/kg body weight); thereafter, the effect on cholesterol was plateaued.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies reported that the effects of tocotrienols and tocotrienol-rich fractions on lipid metabolism in animals [26]- [29] and humans [30]- [33]. The mechanism of the hypocholesterolemic effect of tocotrienols was revealed as the suppression of 3-Hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase activity and inhibition of expression of HMGCoA reductase mRNA [21] [34].…”
Section: Discussionmentioning
confidence: 99%
“…41 Experimental data from the study of hamsters are in agreement. 42 What added to the interest in tocotrienol as a cholesterol-lowering nutrient in humans was a concurrent independent study reporting the hypocholesterolemic effects of palmvitee. 43 Each palmvitee capsule contained approximately 18, 42, and 240 mg of tocopherols, tocotrienols, and palm olein, respectively.…”
Section: Hypercholesterolemic Effectsmentioning
confidence: 99%